Clinical features of chronic pancreatitis at elderly patients with severe mesenteric atherosclerosis - O. S. Shifrin; I. A. Sokolina; T. L. Lemina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
Aim of investigation. To study clinical features of chronic pancreatitis in patients with severe mesenteric atherosclerosis (calcification of celiac trunk).Material and methods. Overall 290 patients with chronic pancreatitis have been investigated. According to alcoholic and biliary etiology of disease, signs that was revealed at computer tomography with bolus contrast injection (calcification of ostium of celiac trunk and superior mesenteric artery), 43 patients were selected to the group with «ischemic component».Results. Patients of this group were characterized by series of features: older age, lower intensity of pain, higher frequency of ischemic heart disease and systemic hypertension. Gastroduodenal erosions with relative resistance to drug treatment were more frequently diagnosed in these patients.Conclusion. At elderly patients with chronic pancreatitis and calcification of mesenteric blood vessels, with respect to frequent constipation tablet pancreatin agents (Mezym® 10000) have high efficacy in treatment of abdominal pain.